2010
DOI: 10.1080/09603100903299675
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity aversion and rational herd behaviour

Abstract: This article reviews the literature on herd behaviour in financial markets in the context of the sequential trading model and points out the importance of incorporating ambiguity into the framework. Although Ford et al. (2005) have applied the Choquet-expected-utility theory to analyse the relationship between ambiguity and herd behaviour, their model does not allow for the separation between ambiguity and ambiguity aversion, therefore how ambiguity and ambiguity aversion affect herd behaviour cannot be analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Because traders may change their beliefs upwards as prices rise, we expect asset prices not to exhibit the same type of dramatic crashes in the ambiguity, as in the risk, treatment. This prediction also relates to the models assessing the impact of ambiguity on herding in financial markets (e.g., Dong et al, 2010;Ford et al, 2013). These works stress that the conditions for the formation of bubbles in a herding model à la Avery and Zemsky (1998) are less stringent in the case in which ambiguity in the fundamentals is introduced.…”
Section: Conjecturesmentioning
confidence: 69%
See 1 more Smart Citation
“…Because traders may change their beliefs upwards as prices rise, we expect asset prices not to exhibit the same type of dramatic crashes in the ambiguity, as in the risk, treatment. This prediction also relates to the models assessing the impact of ambiguity on herding in financial markets (e.g., Dong et al, 2010;Ford et al, 2013). These works stress that the conditions for the formation of bubbles in a herding model à la Avery and Zemsky (1998) are less stringent in the case in which ambiguity in the fundamentals is introduced.…”
Section: Conjecturesmentioning
confidence: 69%
“…Their general finding is that, in the presence of ambiguity, herding in financial markets can occur under a broader set of information conditions than envisioned by Avery and Zemsky (1998). Dong et al, (2010) has also shown that herding may be more likely in the presence of traders who have heterogenous attitudes towards ambiguity.…”
Section: Ambiguity In Financial Marketsmentioning
confidence: 99%
“…Here, we do not specify whether the follow-own-signal behavior will increase or decrease with uncertainty as one could argue in either direction based on previous findings: the sequential trading model of Dong et al (2010) suggests that the tendency to herd increases under increased uncertainty, which could suggest a decrease in follow-own-signal behavior under increased uncertainty. However, the findings of Celen and Kariv (2004) and Kubler and Weizsacker (2004) may suggest the opposite.…”
Section: Hypothesis Developmentmentioning
confidence: 97%
“…This study follows the definition of uncertainty in Knight (1921). Dong et al (2010) also follow the concept of Knightian uncertainty in their sequential trading model, where they define uncertainty of a stock's returns as characterized by the uncertainty about its distributions, such that a stock with three possible distributions about its returns has a higher uncertainty than a stock with two distributions. This is also the definition we use to implement uncertainty.…”
Section: Notesmentioning
confidence: 99%
“…Hasil penelitian menunjukkan bahwa, selain risiko pasar dan ketidakpastian tingkat perusahaan, kecenderungan analis untuk herding meningkat dengan ketidakpastian agregat (M. C. Lin, 2018). Secara khusus, herding tampaknya didorong terutama oleh ketidakpastian pasar, kondisi pasar yang ekstrem dan periode arus informasi yang tinggi (Arjoon & Bhatnagar, 2017;Bernales et al, 2016;Bhaduri & Mahapatra, 2013;Bouri, Gupta, & Roubaud, 2019;Cajueiro & Tabak, 2009;Dong, Gu, & Han, 2010;Indārs et al, 2019;Lan, 2014;Lao & Singh, 2011;Lindhe, 2012;Vo & Phan, 2016). Investor cenderung melakukan herding lebih dekat ketika mereka menghadapi risiko volatilitas tinggi (Al-Shboul, 2012;Balcilar et al, 2013;Bernales et al, 2016;Humayun Kabir & Shakur, 2018;Vo & Phan, 2016).…”
Section: Metode Penelitianunclassified